Photo Degradation of Ketoprofen Using Titanium Dioxide as Catalyst - Yetti, Rina Desni; *, Safni; Rivai, Harrizul (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Research on the degradation of pure ketoprofen and tablets by means of photolysisusing ultraviolet light and titanium dioxide catalysts has been performed. Ketoprofen and itsdegradation results were analyzed by ultraviolet spectrophotometers at 260 nm and highperformance liquid chromatography. Degradation of ketoprofen is done by photolysis usingultraviolet A (366 nm) and ultraviolet C (254 nm) lamps using titanium dioxide (TiO2) ascatalysts at various concentrations, mass and time. The percentage degradation of pureketoprofen and tablets using UV A photolysis method and TiO2 15 mg as catalyst was 51.04% and 48.11 %, respectively, after 180 min. The percentage degradation of pure ketoprofenand tablets using UV C photolysis method and TiO2 15 mg as catalyst was 91.08 % and 89.11%, respectively, after 120 min. The results showed that photolysis method with UV C wasbetter to degrade ketoprofen than UV A with the addition of TiO2 as catalyst. The residualanalysis of ketoprofen was performed by high performance liquid chromatography using C18column (150 mm x 4.6 mm), the mobile phase was acetonitrile: 0.2 % acetic acid (45: 55),the flow rate was 1.2 mL / min. Chromatogram showed a decrease in peak ketoprofen and theemergence of new peaks during ketoprofen degradation process.